1999
DOI: 10.1210/endo.140.3.6589
|View full text |Cite
|
Sign up to set email alerts
|

Function of Stem Cell Factor as a Survival Factor of Spermatogonia and Localization of Messenger Ribonucleic Acid in the Rat Seminiferous Epithelium1

Abstract: To address the possibility that stem cell factor (SCF) is a paracrine regulator of germ cell development in the adult rat testis, stage-specific distribution of SCF messenger RNA (mRNA) was investigated with Northern blot and in situ hybridization analyses. The highest levels of SCF mRNA were found in stages II-VI of the rat seminiferous epithelial cycle, whereas the lowest levels were in stages VII-VIII. Intermediate levels of SCF mRNA were detected in stages IX-XIV-I of the cycle. The expression of the SCF g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Pathways-It has been proposed that SCF acts as a survival factor that prevents apoptosis in differentiating spermatogonia (13,19,34). In line with this we observed that during the 24 h of culture, concomitantly with the increase of the metaphase counts, SCF decreased the frequency of cells showing morphologies typical of apoptosis (Fig.…”
Section: Scf-mediated Prevention Of Spontaneous Apoptosis In Culturedsupporting
confidence: 86%
See 2 more Smart Citations
“…Pathways-It has been proposed that SCF acts as a survival factor that prevents apoptosis in differentiating spermatogonia (13,19,34). In line with this we observed that during the 24 h of culture, concomitantly with the increase of the metaphase counts, SCF decreased the frequency of cells showing morphologies typical of apoptosis (Fig.…”
Section: Scf-mediated Prevention Of Spontaneous Apoptosis In Culturedsupporting
confidence: 86%
“…It has been proposed that SCF acts merely as a survival factor that prevents apoptosis in differentiating spermatogonia, which are assumed to be intrinsically committed to proliferate (13,19,34). We actually found that SCF addition also partially inhibits apoptosis occurring in germ cells from 8-dayold mice after 24 h of culture.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Expression levels and phosphorylation status of pocket proteins in the cultured seminiferous tubules in the presence or absence of SCF When the seminiferous tubules from stage XII of the epithelial cycle were cultured in the presence of SCF (100 ng/ml), the [ 3 H]-thymidine uptake was signi®-cantly elevated after 48 and 72 h culture in vitro in comparison to the controls (Hakovirta et al, 1999). Moreover, in the absence of SCF, the number of apoptotic germ cells was much higher than in the presence of stem cell factor during 8 ± 72 h culture (Yan et al, 2000c).…”
Section: Expression Of Pocket Proteins P107 and P130 During Testiculamentioning
confidence: 99%
“…Stem cell factor enhances pRb expression and phosphorylation in vitro and blockade of SCF/c-kit interaction in vivo suppresses levels and phosphorylation of pRb: correlation with spermatogonial proliferation and apoptosis It is known that in the presence of stem cell factor (SCF) [ 3 H]-thymidine incorporation of the seminiferous tubules from stage XII was enhanced and apoptosis was suppressed signi®cantly after 48 ± 72 h culture in vitro in comparison to controls (Hakovirta et al, 1999). Recent studies also show that in the presence of SCF both mitotic and meiotic DNA synthesis of germ cells could be maintained in vitro for at least 72 h and germ cells could pass through meiosis and further dierentiate into spermatids (Vincent et al, 1998).…”
Section: Cell Type-specific Expression Of Pocket Proteins During Testmentioning
confidence: 99%